Financial Advice Seeking: A Review of the Barriers and Benefits. Issue 4 (17th August 2020) - Westermann, Steffen; Niblock, Scott J.; Harrison, Jennifer L.; Kortt, Michael A.
Abstract : This paper reviews the literature on the perceived individual‐level demand‐side barriers to and benefits from seeking and following financial advice. Our review reveals that poor financial literacy, lack of trust and financial adviser anxiety have all been found to dissuade individuals from pursuing professional financial advice. The limited literature on the effectiveness of financial advice in terms of financial well‐being suggests a positive link. However, no study has collectively examined the influence of financial literacy, trust and financial adviser anxiety on financial advice seeking and well‐being in Australia. We conclude by discussing further gaps, policy recommendations, the recently introduced amendments to the Australian Corporations Act and several directions for future research, which may provide theoretical and practical benefits to policy‐makers, industry professionals, academics and individuals.